Isolation and Identification of Polyethylene Terephthalate Degrading Bacteria from Shatt Al-Arab and Sewage Water of Basrah City - Eman Aboob Mukhaifi; Hala Sabry Al-Atbi; Suhyila Fadhil Ali (مجلة بغداد للعلوم, 2023)
Biodegradation is utilizing microorganisms to degrade materials into products that are safe for the environment, such as carbon dioxide, water, and biomass. The current study aims to isolate and characterize bacteria with polyethylene terephthalate (PET) degradation ability isolated from Shatt al-Arab water and sewage from Basra, the bacteria were identified as Klebsiella pneumonia. According to the findings, the isolates showed a highly significant difference in degradation of PET (24% during 7 days) and the percent of degradation increased to 46% at 4 weeks compared to the control. The study also involved determining the optimum temperature of K. pneumonia growth, which was 37°C, while the preferred pH was 7-8. The research revealed that PET biodegradation by K. pneumonia can be used as a suitable and environmentally friendly tool.